JEZREEL REVEALED IN LASER SCANS: A Preliminary Report of the 2012 Survey Season - Ebeling, Jennie R. (Near Eastern archaeology, 2012)
In June 2012, the Jezreel Expedition team conducted a landscape survey of 3 km2 of greater Jezreel to the west, north, and east of Tel Jezreel in Israel's Jezreel Valley. In this preliminary report, we review the results of previous excavations and surveys at the site, briefly present the types of features we documented on the landscape, and discuss our plans for future excavation seasons. We also describe the results of an airborne LiDAR laser scan we commissioned in February 2012—the first time this technique has been used by an archaeological project in Israel—and the historical background of an uncultivated area near ʿEin Jezreel that will be a focus of future excavations.